3D visibility analysis as a tool to validate ancient theatre reconstructions: the case of the large Roman theatre of Gortyn - Maria Cristina Manzetti (Virtual Archaeology Review)
With the diffusion of Virtual Archaeology, many projects in the field of Cultural Heritage attempt to virtually reconstruct historical buildings of different types. Unfortunately, some of these 3D reconstructions still have as principal aim to impress the external users, while the correct interpretation of the buildings modeled is much more important in the domain of archaeological research. Still more critical is the situation when we have to encounter a reconstruction of a monument which is not visible anymore, or which consists only of few architectural remains. The main purpose of this paper is to introduce an innovative methodology to verify hypothetical scenarios of 3D architectural reconstructions, specifically for ancient theatres. In very recent time 3D visibility analysis applied to archaeological context using ArcGIS has been developed, in particular about social-urban studies. In this paper, visibility analysis in 3D contexts is used as an additional instrument to correctly reconstruct architectural elements of the large Roman theatre of Gortyn, in Crete. The results indicate that the level of visibility of the stage, and consequently of the presumed actors, from some of the more representative sectors of the cavea, is of crucial importance for leading to a right reconstruction model of the theatre.